Northern Shrimp (Pandalus borealis) on Flemish Cap Surveys 2008 - Casas-Sánchez, José Miguel (2008)
A stratified random bottom trawl survey on Flemish Cap was carried out from June 18th to July 22th 2008. The area surveyed was extended up to depths of 800 fathoms (1400 meters) following the same procedures as in previous years and increasing the number of hauls planned (175). A total of 167 valid hauls were made by the vessel R/V Vizconde de Eza with the usual survey gear (Lofoten), 115 up to 730 meters depth. The general indexes for shrimp were estimated taken into account the traditional swept area (strata 1-19, up to depths of 730 m) and the total area surveyed (strata 1-34, up to depths of 1400 m). The results concerning shrimp are presented and compared to those from previous years of the same series. The biomass and abundance in 2008 decreased markedly from 2007 (41% and 35% respectively) to levels prior to 1998. In the other side, as in the last years (2004-2007) the youngest specimens (age 1) didn't appear in the catches, and they were weakly presents in the small mesh size bag attached to the cod-end of the main gear, suggesting the absence of any strong year classes since 2003.